Deteksi Ionisasi Udara Akibat Radioaktivitas Americium-241 (Am-241) Melalui Parameter Kelistrikan - Tedi Sumardi; Siti Nurasiah (CV. Multi Kreasi Media, 2022)
Radioactivity is the decay of radioactive substances due to the interaction between radioactive subtances and atoms or molecules in the air to form air ionization. In this study, air ionization detection was carried out by observing its changes in voltage, current, and distance from the radiation source that generated by Am-241 on vertical and horizontal positions. The experiment was repeated by 3 times at each position of Am-241 depends to electrodes. The results showed a change in the voltage due to the presence of Am-241 in different positions. This related with the strength of electric current and the distance of Am-241 positions, where the farther position of Am-241 has the stronger electric current. Thus, the alteration of electric current and voltage proved that radiation has been emitted by Am-241.